Social Capital as a Strategy to Sustain Women's Functionality in TNKS Pal Delapan Forest Suburbs Rejang Lebong Regency - Yunilisiah Yunilisiah; Tamrin Bangsu; Desy Afrita (Syntax Corporation Indonesia, 2023)
This study focuses on social capital as a strategy for women's functionality in the forest suburbs of TMKS Pal Eight, Rejang Lebong Regency. Communities, especially women who live around the periphery of the forest, have undergone changes in the area of control of agricultural land, because there are provisions for the boundaries of the TNKS forest area and this is related to social functionality. The purpose of social capital research as a strategy to maintain the social functionality of women living on the edge of TNKS Forest is a qualitative research study that will provide the necessary contribution as a foundation and pattern of problem solving related to women maintaining social functionality in social life. Participant data collection through direct observation and in-depth interviews and documentation. The data were analyzed with an interactive model based on qualitative interplay inductively with an emic approach. The results showed that social capital is a resource that is used as a functional strategy for women tending to be based on land tenure. The area of land tenure after the TNKS area is determined, women in the family unit manage customary forest land communally. For them, forests are an element of sustainable life and forests not only function economically and socially, but also have spiritual value. Households are narrow and unbiased with a pattern of relationships in carrying out social functionality in the form of economic working group units based on region of origin and place of residence.